S65 Quantification of 'whole lung' pulmonary eosinophilic inflammation using radiolabelled autologous human eosinophils. (15th November 2017) - Farahi, N; Loutsios, S; Tregay, N; Wright, AKA; Lok, LSC; Gillett, D; Cullum, I; Simmonds, RP; Summers, C; Wong, A; Solanki, CK; Buscombe, J; et al.
Abstract : Background: Eosinophils are key mediators of allergic inflammation. The ability to localise and quantify eosinophilic inflammation in vivo would facilitate patient endotyping and evaluation of eosinophil-targeted therapeutics. We aimed to quantify eosinophil distribution and organ-specific uptake in healthy subjects, asthmatics, and patients with focal pulmonary eosinophilic inflammation. Methods: We injected autologous radiolabelled eosinophils into 8 healthy volunteers, 15 asthmatics (7 obese and 7 non-obese), and 3 patients with focal eosinophilic inflammation and monitored eosinophil distribution (planar imaging, single photon emission computed tomography – SPECT)/CT). Lung accumulation of technetium-99 m-labelled eosinophils was quantified (Patlak-Rutland analysis). Whole body indium-111-labelled eosinophil distribution and loss were further assessed in 5 healthy volunteers and 7 asthmatics using a whole body counter. Findings: Pulmonary eosinophil clearance was increased in patients with focal eosinophilia (0·0033 ml/min/ml; 95% CI −0·005–0·011; p=0.02) compared to asthmatics (0·0007 ml/min/ml; 95% CI 0·0003–0·0010; p=0.14) and controls (0·0003 ml/min/ml; 95% CI −7·5 × 10 –5 –0·0008). Absolute lung eosinophil migration was elevated in patients with focal inflammation (5932 eosinophils/min/ml; 95% CI −14351–26215, p=0.01) and asthma (364 eosinophils/min/ml; 95% CI 38–689; p=0.03) versus healthy volunteers (38 eosinophils/min/ml; 95% CI −11–87). Stratification of asthmatics based on BMI revealed increased pulmonary eosinophil clearance in obese (0·001 ml/min/ml; 95% CI 0·0007–0·001; p=0.02) versus non-obese asthmatics (0·0003 ml/min/ml; 95% CI −0·0002–0·0009). Interpretation: Eosinophil radiolabelling can quantify pulmonary eosinophilic inflammation, with the potential for patient endotyping and testing eosinophil-targeted treatments. Funding: Medical Research Council, Wellcome Trust, Asthma UK, Cambridge NIHR Biomedical Research Centre.